Sizing renewable energy systems with energy storage systems in microgrids for maximum cost-efficient utilization of renewable energy resources. (April 2020) - Al-Ghussain, Loiy; Samu, Remember; Taylan, Onur; Fahrioglu, Murat
Highlights: ESS sizing affects significantly the technical and economic feasibilities of RESs. Hybrid ESSs could play a significant role in the development of RES-based microgrids. Hybrid RESs with hybrid ESSs can cover the majority of the communities' demand in affordable way. Abstract: The hybridization of renewable energy systems (RES) and further integrating them with Energy Storage Systems (ESS) can help improve the RESs' reliability and reduce the mismatch between energy consumption and generation profiles. The main aim of this study is to suggest a sizing methodology for the RES components with various ESS scenarios in a microgrid through techno-economic feasibility analysis. Although the suggested methodology is flexible to include several RESs and ESSs, the methodology is demonstrated to compare the techno-economic performance of Wind and Photovoltaic (PV) energy systems under four different ESS scenarios; (i) no ESS, (ii) Pumped Hydro Storage (PHS), (iii) Hydrogen Fuel Cell (HFC), and (iv) hybrid ESS (PHS/HFC). The optimal RES configuration is determined by maximizing the RES fraction while equating the Cost of Electricity (COE) to the national utility tariff. However, in the event that there is no feasible system configuration that satisfies the mentioned criteria, the main objective becomes maximizing the RES fraction at the lowest attainable COE. This study outlines that the incorporation of PHS and HFC with the PV/Wind hybrid system increased the demand-supply fraction from 46.5%–89.4% and the RES fraction from 62.6%–91.8% with COE equals to 0.175 USD/kWh.